ANALISIS PRODUKSI USAHA PENGASAPAN IKAN DI DESA KOTO MESJID KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Sari, Yesi Purmita; Harahap, Azwar; ', Harlen (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to know the capital, raw materials and labor effect of positive and negative factors of production and to know what is the most dominant affect of curring fish industrial production at Koto Mesjid Kampar XIII District of Kampar.The population in this research is the whole industry entrepeneur fogging producing smoked fish/ fish salai in the village of Koto Mesjid that addup to 10 industry. Sampling techniques in the study using census by taking the whole of curing fish bussines. Analysis of the method used is descriptive quantitative analysis method of multiple linear production function which uses a Cobb-Douglass.Cobb-Douglass analysis results showed that the estimated production function model is LnY = -9.358 + -0.018LnX1 + 2.756 LnX2 + 0.001 LnX3. The coefficient of determination (R2) by thethird of dependents variable against independent variable is 0.940. which means of the influence of capital, raw materials and labor against of curring fish bussines production in the village of koto mesjid is 94%, while the remaining 6% is affected by other factors that are not discussed in this study. Simultaneous regressipon test (F test) shows that the whole of the independent variables in the meticulous namely capital, raw materials and labor are positive and significant effect against variable is of curing fish industrial production at Koto Mesjid, and the dominant variable influecing of curing fish industrial production at Koto Mesjid is the raw material.keywords : curing fish industrial production, capital, raw material, labor.